1997
DOI: 10.1111/j.1600-0447.1997.tb09659.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on switching patients with schizophrenia to risperidone treatment

Abstract: This study examined one possible strategy for switching patients to treatment with risperidone involving immediate cessation of current neuroleptics and gradual withdrawal of anticholinergic treatments. All patients received risperidone monotherapy for at least 4 weeks. Side-effects and symptoms were rated and successful switching was defined as completion of the study with no consistent worsening in any rating scales. Of the 41 patients entered, five withdrew for reasons unconnected with the study. Of the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…In a study that did not have a gradual crossover design, patients receiving oral or depot formulations of conventional antipsychotics were switched directly to oral risperidone (Kirov et al, 1997). Patients switched from conventional depot formulations had the best outcomes, and the investigators suggested that this occurred because the gradual tapering of medication that takes place when a depot is discontinued provided sufficient (but not excessive) protection against breakthrough symptoms while oral risperidone was beginning to exert its protective effect.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a study that did not have a gradual crossover design, patients receiving oral or depot formulations of conventional antipsychotics were switched directly to oral risperidone (Kirov et al, 1997). Patients switched from conventional depot formulations had the best outcomes, and the investigators suggested that this occurred because the gradual tapering of medication that takes place when a depot is discontinued provided sufficient (but not excessive) protection against breakthrough symptoms while oral risperidone was beginning to exert its protective effect.…”
Section: Discussionmentioning
confidence: 97%
“…Although investigators have reported that patients switched from a conventional depot formulation to oral risperidone have not found their oral regimen burdensome (Kirov et al, 1997;Desai et al, 1999), the need to take oral medication may be more of a problem outside the context of a clinical trial, when patients are less likely to be closely supervised and when those who are less disposed to be compliant are receiving treatment (Barnes and Curson, 1995). Given that patients with a history of poor compliance are especially likely to be recommended for treatment with long-acting risperidone (Kane et al, 1998), the lack of the need for routine oral supplementation at the start of treatment, as demonstrated in this study, is particularly valuable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The beneficial effects of risperidone on the negative symptoms of schizophrenia are most likely the result of a predominant affinity for 5HT 2 receptors, while its adequately low D 2 receptor occupancy is beneficial to the treatment of positive symptoms and results in a low occurrence of extrapyramidal symptoms [1,2]. Meltzer [3] indicated that the ratio of 5HT 2 to D 2 -receptor-binding affinities has predictive value for identifying atypical neuroleptics.…”
mentioning
confidence: 99%
“…Risperidone is a benzisoxazole derivative with combined 5HT 2 and D 2 -receptor-blocking properties. The beneficial effects of risperidone on the negative symptoms of schizophrenia are most likely the result of a predominant affinity for 5HT 2 receptors, while its adequately low D 2 receptor occupancy is beneficial to the treatment of positive symptoms and results in a low occurrence of extrapyramidal symptoms [1,2].…”
mentioning
confidence: 99%